Poorly evaluated factors in satisfaction surveys applied to users of Primary care in Latin America - Reynaldos-Grandón, Katiuska Lidice (2017)
The aim of this manuscript is to identify poorly evaluated factors in user satisfaction surveys applied to populations in primary care centers in Latin America. The methodology consists of a literature review. The bibliographic search was done in the databases LILACS, SCIELO, REDALYC, CUIDEN, REDIB, DIALNET, PUBLINDEX and EBSCO. Initially, 21 studies were obtained, of which eight were selected according to the inclusion criteria. The main outcome is that the main poorly evaluated factors are the following: access to care, timeliness of care, waiting time,  pre-service procedure delay, staff adequacy, delivery of free medication, information on legal rights and duties, health problem resolution, adjustment of the schedule to the needs of the users, infrastructure, environment and comfort and, finally, the clear indications of the prescription. It is concluded that the importance of measuring user satisfaction, especially in primary care, is indisputable because it is the gateway to the health context. Identifying factors that are poorly evaluated in surveys, allows for interventions to be guided by needs improvement, as well as to satisfy the patient's expectations and to improve the quality of care.